DEVELOPMENT OF IMPROVISATION SKILLS IN MUSIC EDUCATION - Болдуєва, М.; Стотика, О. (SWorldJournal, 2022)
This paper considers and reveals the basic foundations for children to learn improvisation in music lessons. Relying on the experience of educators who research this area helps us to summarize the material and find the easiest ways to teach children to im